(untitled) (Annals of Medical Research, 2021)
Aim: Inguinal hernia repair is one of the most common surgeries in General Surgery practice. Although different surgical procedures have been used for the treatment of hernias, minimally invasive approaches are increasingly preferred to manage hernia repair. The aim of this study is to evaluate our 2-year laparoscopic transabdominal preperitoneal (TAPP) hernia repair outcomes. Materials and Methods: The data of patients who were diagnosed with inguinal hernia and who underwent the TAPP procedure between the dates of December 2017 and December 2019 were evaluated retrospectively.Results: Ninety-six patients were included in this study. Of these patients, 89 were male and 7 were female. The mean age was 46 (range between 22 and 76). Fifty six (58.3%) cases had right inguinal hernia, 22 (22.9%) cases had left inguinal hernia and 18 (18.7%) cases had bilateral inguinal hernia. The mean hospital stay was 1.06 (1-3) days. In the early postoperative period we observed for minor complications such as seroma, hydrocele, epididymitis, and hematoma. Three patients experienced chronic pain. Recurrence was observed in 3 patients during follow-up. No major complications were seen.Conclusion: Laparoscopic hernia repair is an efficient and attractive method because it offers better cosmetic results, earlier recovery, less pain, shortened hospital stay and early return to daily activities. However, the learning process for performing this procedure is more difficult than for the open method. Therefore, the learning curve of laparoscopic hernia surgery is longer. It has been reported that there is a difference in the rate of recurrence in surgeons trained in the laparoscopic method after specialization. We believe that this method can be applied safely by people who have received laparoscopic hernia surgery training.